Особенности гистологического строения кожи антилопы канна (Taurotragus oryx Pall.) - Кацы, Г.Д.; Королев, Н.А. (Вестник зоологии, 1974)
It was established that Taurotragus oryx Pall. females (domesticated animals) possess thicker epidermis and greater number of glands and area of secretory surface of sebaceous glands per 1 cm2 of skin; thickness of papillary and reticular layers as well as total thickness of skin and area of secretory surface of sudoriferous glands is less than those in cows of the Red steppe breed (domestic animals).